The Impact of the COVID-19 Pandemic on Communication Studies: Bibliometric Analysis - Aysel Kurnaz (Selçuk İletişim)
This research aims to examine which issues are mainly carried out in international articles published in journals that direct the field of communication during the COVID-19 pandemic process and how many of these studies are related to COVID-19 through the bibliometric analysis method. For this purpose, the top 20 journals with high impact factors in communication were evaluated according to the Journal Citation Reports (2019) and Scimago Journal & Country Rank (2019) in the Q1 rank. The articles published in the relevant journals between January 1, 2020 - April 20, 2021, have been accessed through the Web of Science database. As a result of the analyses performed using R software, a total of 1613 articles were examined, and it was determined that the number of articles related to COVID-19 was 36. 25 of 36 works on COVID-19 were published in the “Social Media + Society” journal. It was observed that 14 of the first 20 journals did not publish articles on COVID-19. It is seen that 40% of the top 10 authors who published most in the field of communication during the relevant research period were from the University of Amsterdam, and 75% of the authors who worked on COVID-19 were from the University of Zurich. While the main keywords in the communication literature were "social media," "journalism," "news," "Twitter," "Facebook," and "Instagram," the concepts of "social media," "misinformation," and "contact tracing" came to the fore in COVID-19 related studies.